Melatonin: An Eco-Friendly Preservative for Improving Post-Harvest Quality and Longevity of Cut Flowers - Toan Nguyen; Suong Ha (Horticulturae)
Post-harvest quality and longevity of cut flowers are critical factors influencing customer satisfaction and purchase decisions. Maintaining post-harvest quality and ensuring a long vase life (VL) present significant challenges to the floriculture industry due to the perishable nature of cut flowers. Recent studies have demonstrated the potential of melatonin (MT), a multifunctional biomolecule, to improve the post-harvest quality and longevity of floricultural products. This review highlights recent advances in the application of MT to improve the longevity and post-harvest quality of cut flowers. The physiological, biochemical, and molecular mechanisms underlying MT’s effects, along with various application methods, are discussed. Furthermore, current challenges and knowledge gaps are identified, and future research directions are proposed to explore MT’s potential in diverse flower species and its practical application in the cut flower industry.